2023
DOI: 10.1002/pc.27623
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and extrinsic self‐healing fiber‐reinforced polymer composites: A review

Juntao Wang,
Jun Tang,
Dingding Chen
et al.

Abstract: With their high specific modulus, high specific strength and designability, fiber‐reinforced polymer (FRP) composites have replaced or surpassed traditional metallic materials in a wide range of applications. However, the polymer matrix of commonly used FRP composites is usually a thermosetting polymer that is difficult to rework once formed, which implants a substantial challenge for the repair and recycling of composites. Self‐repair, as an emerging method of repairing polymer‐based materials, has the advant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 116 publications
0
7
0
Order By: Relevance
“…Furthermore, before the printing process of 3D‐printed CFRCs, introducing self‐healing material to treat the surface of continuous fibers might improve the impregnation quality. After this pre‐treatment process, composites had the potential to heal interface defects formed during loading 45,72 …”
Section: Fracture Toughness Improvement Methodsmentioning
confidence: 99%
“…Furthermore, before the printing process of 3D‐printed CFRCs, introducing self‐healing material to treat the surface of continuous fibers might improve the impregnation quality. After this pre‐treatment process, composites had the potential to heal interface defects formed during loading 45,72 …”
Section: Fracture Toughness Improvement Methodsmentioning
confidence: 99%
“…1 At present, selfhealing polymers are divided into two main categories. 2 One is the extrinsic self-healing polymer, which heals the damage through the pre-embedded healing agent in the polymer matrix. The other is the intrinsic self-healing polymer, which heals damage through the disconnection and formation of dynamic intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Self-healing polymer materials have been widely studied for their ability to effectively extend service life . At present, self-healing polymers are divided into two main categories . One is the extrinsic self-healing polymer, which heals the damage through the pre-embedded healing agent in the polymer matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Since White et al 14 first demonstrated the concept of selfhealing materials in 2001, there has been a great deal of research on materials with damage self-healing capability. Currently, self-healing materials can be primarily divided into two categories 15 : (a) the intrinsic type, which uses thermoplastic polymer blending or the reversible reaction of the matrix itself, and is stimulated by external conditions (e.g., heating, pressurization, etc.) to repair damage.…”
Section: Introductionmentioning
confidence: 99%